PREVALENCE OF ABO/RH BLOOD TYPES AMONG FEMALES WITH EATING DISORDERS IN HYDERABAD, PAKISTAN: AN ANALYSIS UTILIZING THE EAT-26 QUESTIONNAIRE - Farhanuddin, Syed; Ahmed Warsi, Jamshed; Mangi, Rozina; Waheed, Kiran; Rani, Keenjahr; Noor, Naila (Annals of Allied Health Sciences, 2025)
Objective: To assess the proportion of various blood groups and how those groups relate to one another. Material & Methods: The current study was conducted by the Department of Physiology at Sindh University Jamshoro from June 2023 to December 2023 after obtaining ethical review. A total of 210 (n = 210) female participants took part in the study. The study pinpoints the prevalence of eating disorders with reference to junk food and/or breakfast-taking habits in adolescent females. A survey was conducted using the EAT-26 questionnaire, which was distributed in different restaurants in Hyderabad. A score greater than 20 was considered positive for the eating disorder. The blood groups were evaluated by the glass slide method (antigen-agglutination test) with the use of Anti-Sera A, Band O (Rapid Labs UK). The test was repeated to minimize the error. Results: The proportion of Eds was 38.57% in the B blood group, with an odds ratio of 1.78 and a P value of 0.36 showing no significance between blood groups. The B blood group was predominant. Conclusion: It is concluded that blood group B is associated more with eating disorders.